2012
DOI: 10.1088/0957-0233/24/2/024006
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous 3D measurement of the translation and rotation of finite-size particles and the flow field in a fully developed turbulent water flow

Abstract: We report a novel experimental technique that measures simultaneously in three dimensions the trajectories, the translation and the rotation of finite-size inertial particles together with the turbulent flow. The flow field is analyzed by tracking the temporal evolution of small fluorescent tracer particles. The inertial particles consist of a super-absorbent polymer that renders them index and density matched with water and thus invisible. The particles are marked by inserting at various locations tracer part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
59
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 37 publications
2
59
0
Order By: Relevance
“…We consider in particular the influence of the large-scale (inhomogeneous) flow structure and its impact on the particle's dynamics. This complements recent studies [11,12] which have focused on the local flow surrounding the particles, but ignoring the influence of anisotropy and inhomogeneity of the flow at large scales. Our motivation stems from the possibility that particles with sizes close to the integral scale may be sensitive to the kinetic energy injection details and hence the largescale structure of the flow.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…We consider in particular the influence of the large-scale (inhomogeneous) flow structure and its impact on the particle's dynamics. This complements recent studies [11,12] which have focused on the local flow surrounding the particles, but ignoring the influence of anisotropy and inhomogeneity of the flow at large scales. Our motivation stems from the possibility that particles with sizes close to the integral scale may be sensitive to the kinetic energy injection details and hence the largescale structure of the flow.…”
Section: Introductionsupporting
confidence: 73%
“…Very few studies have been carried out for particles with size comparable to the integral length scale [10][11][12], despite their potential importance for applied situations [13,14]. It has recently been shown that such particles show a very intermittent dynamics of both translation and rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Many physical experiments rely on image analysis to obtain these parameters from experimental data (Bovik 2010;Meyer et al 2013). Most of these systems capture translation and retrieve orientation from relative motion of translating nodes (Klein et al 2013). In the more elementary forms, the translation of nodes could be used to determine the velocities of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are often difficult to scale-up due to issues related to long-time properties of the suspending solution, thermal stability, handling and cost. Super-absorbent hydrogel particles in water, used in this study, can be advantageously used for performing RIM-PIV as previously shown in Klein et al [13], Byron and Variano [14] and Harshani et al [15]. The mechanical properties of commercially available spherical hydrogel particles are discussed in Dijksman et al [16].…”
Section: Introductionmentioning
confidence: 91%